Permit but discourage regulating excessive consumption - Bogart, W. A. (William A.) (New York ; Oxford : Oxford University Press, 2011)
This text analyzes the effectiveness of law in controlling excessive consumption. It engages theoretical discussions concerning the effectiveness of legal intervention, especially regarding 'normativity', the relationship between law and norms.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 12, 2011).
Keywords: Gambling -- Law and legislation; Gambling -- Taxation -- Law and legislation; Liquor laws; Alcohol -- Taxation -- Law and legislation